1986
DOI: 10.1177/088307388600100404
|View full text |Cite
|
Sign up to set email alerts
|

Cerebro-Oculo-Hepato-Renal Syndrome (Arima's Syndrome): A Distinct Clinocopathological Entity

Abstract: Three children with Leber's congenital amaurosis, agenesis of the cerebellar vermis, and infantile polycystic kidneys are described. The common clinical findings of three unrelated patients (two boys and one girl) included severe visual impairment from early infancy, profound psychomotor retardation, hypotonia, nystagmus, characteristic facial appearance with blepharoptosis, and progressive chronic renal insufficiency. The two boys died of uremia at ages 13 and 12 years. The common pathological findings in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…The kidney abnormalities were almost always severe. Although previous reports have generally described the renal abnormality as "polycystic kidneys," the few detailed pathological descriptions are clearly more compatible with CDK [Dekaban, 1969;Ivasrsson et al, 1993;Matsuzaka et al, 1986]. Liver fibrosis was documented in 4 of 21 patients in this group.…”
Section: Cerebello-oculo-renal (Hepatic) Syndromesmentioning
confidence: 48%
See 3 more Smart Citations
“…The kidney abnormalities were almost always severe. Although previous reports have generally described the renal abnormality as "polycystic kidneys," the few detailed pathological descriptions are clearly more compatible with CDK [Dekaban, 1969;Ivasrsson et al, 1993;Matsuzaka et al, 1986]. Liver fibrosis was documented in 4 of 21 patients in this group.…”
Section: Cerebello-oculo-renal (Hepatic) Syndromesmentioning
confidence: 48%
“…The pathological abnormalities were interpreted as consistent with "tapetoretinal degeneration" [Dekaban, 1969;Ivarsson et al, 1993;. Abnormalities of the kidneys were consistent with CDK, including hypoplasia and dysplasia of cortex and medulla, persistent fetal lobulations, and cysts of variable but often large size throughout the cortex and medulla [Dekaban, 1969;Ivarsson et al, 1993;Kudo et al, 1985;Matsuzaka et al, 1986]. When patients with early death (or last exam at age 2 weeks) are excluded, all patients with CVH and CDK also had retinopathy.…”
Section: Cerebello-oculo-renal (Hepatic) Syndromesmentioning
confidence: 98%
See 2 more Smart Citations
“…Dekaban [1969] reported on 2 sibs with LCA, polycystic kidneys, and brain malformation of autosomal-recessive inheritance as a new syndrome. Arima et al [1971] and Koya et al [1973] reported on patients with LCA, severe psychomotor retardation, agenesis of the cerebellar vermis, and blepharoptosis [see also Kawaguchi et al, 1984;Matsuzaka et al, 1986]. Senior et al [1961] reported on 4 sibs with LCA and nephropathy.…”
Section: Discussionmentioning
confidence: 96%